Backward Dependencies and in-Situ wh-Questions as Test Cases on How to Approach Experimental Linguistics Research That Pursues Theoretical Linguistics Questions - Pablos, Leticia; Doetjes, Jenny; Cheng, Lisa L.-S. (Frontiers in Psychology, 2018)
The empirical study of language is a young field in contemporary linguistics. This being the case, and following a natural development process, the field is currently at a stage where different research methods and experimental approaches are being put into question in terms of their validity. Without pretending to provide an answer with respect to the best way to conduct linguistics related experimental research, in this article we aim at examining the process that researchers follow in the design and implementation of experimental linguistics research with a goal to validate specific theoretical linguistic analyses. First, we discuss the general challenges that experimental work faces in finding a compromise between addressing theoretically relevant questions and being able to implement these questions in a specific controlled experimental paradigm. We discuss the Granularity Mismatch Problem (Poeppel and Embick, 2005)which addresses the challenges that research that is trying to bridge the representations and computations of language and their psycholinguistic/neurolinguistic evidence faces, and the basic assumptions that interdisciplinary research needs to consider due to the different conceptual granularity of the objects under study. To illustrate the practical implications of the points addressed, we compare two approaches to perform linguistic experimental research by reviewing a number of our own studies strongly grounded on theoretically informed questions. First, we show how linguistic phenomena similar at a conceptual level can be tested within the same language using measurement of event-related potentials (ERP) by discussing results from two ERP experiments on the processing of long-distance backward dependencies that involve coreference and negative polarity items respectively in Dutch. Second, we examine how the same linguistic phenomenon can be tested in different languages using reading time measures by discussing the outcome of four self-paced reading experiments on the processing of in-situ wh-questions in Mandarin Chinese and French. Finally, we review the implications that our findings have for the specific theoretical linguistics questions that we originally aimed to address. We conclude with an overview of the general insights that can be gained from the role of structural hierarchy and grammatical constraints in processing and the existing limitations on the generalization of results.